Increased Cardiometabolic Risk in Men with Hypoprolactinemia: A Pilot Study - Robert Krysiak; Karolina Kowalcze; Witold Szkróbka; Bogusław Okopień (Biomolecules)
Low prolactin levels in men predispose them to mood disturbances, sexual dysfunction, and diabetes. The purpose of the current study was to assess cardiometabolic risk in males with hypoprolactinemia. This prospective study included three age-matched groups of young and middle-aged men: individuals with cabergoline-induced hypoprolactinemia (n = 15), cabergoline-treated subjects with prolactin levels within the reference range (n = 20), and untreated men with normal prolactin levels (n = 31). In men with hypoprolactinemia, the cabergoline dose was reduced in order to normalize prolactin concentration. Anthropometric parameters, blood pressure, QRISK3 score; plasma concentrations of prolactin, glucose, insulin, lipids, uric acid, high-sensitivity C-reactive protein (hsCRP), fibrinogen, homocysteine, and testosterone; whole-blood levels of glycated hemoglobin (HbA1C); urinary albumin-to-creatinine ratio (UACR); and carotid intima–media thickness were assessed at baseline and six months later. Men with hypoprolactinemia were characterized by higher body mass index, fat content, waist circumference, systolic blood pressure, fasting and 2 h post-load glucose, HbA1C, HOMA1-IR, uric acid, hsCRP, fibrinogen, homocysteine, and UACR; by lower HDL cholesterol and testosterone; by greater intima–media thickness; and by a higher QRISK3 score than their peers with normal prolactin levels. There were no statistically significant differences in the measured parameters between both groups of men with normal prolactin levels. Normalization of prolactin concentration was accompanied by normalization of biochemical variables, systolic blood pressure, and QRISK3 score. Although cabergoline dose reduction did not cause statistically significant changes in the remaining anthropometric parameters and intima–media thickness, six months later, they did not differ from those observed in the remaining study groups. Our findings suggest that iatrogenic hypoprolactinemia is associated with increased cardiometabolic risk, which is reversible and resolves after the normalization of prolactin levels.